Contractual Procedures in the Construction Industry - Ashworth, Allan, 1944- (Harlow, England ; New York : Pearson, 2012)
This revised edition takes account of the many different contractual procedures now available and the criteria that can be used in the selection of the best options.
Formerly CIP.
Includes bibliographical references (p. [453]-455) and index.
Keywords: Construction contracts -- England; Construction industry -- Law and legislation -- England